Joining Forces or Going It Alone? On the Interplay among External Collaboration Partner Types, Interfirm Governance Modes, and Internal R&D1. Issue 3 (13th October 2014) - Gesing, Judith; Antons, David; Piening, Erk P.; Rese, Mario; Salge, Torsten Oliver
<x xml:space="preserve">Abstract</x> This paper adds to the emerging literature stream advocating a contingency view on open innovation. Drawing on the relational view of the firm, this study sheds light on the complex interplay among collaboration partner types (market‐ and science‐focused innovation partners), governance modes (informal, self‐enforcing and formal, contractual collaboration governance), and internal research and development(R&D). More specifically, it is proposed that the use of governance modes tailored to both the characteristics of each innovation partner type and the specific innovation objectives pursued by the focal firm (incremental and radical new product development) can increase the payoff from innovation collaboration. Moreover, appropriate collaboration governance is expected to reduce the focal firm's vulnerability to possible negative side effects often assumed to be associated with the simultaneous pursuit of external collaboration and internal R&D, among which most notably the not‐invented‐here (NIH) syndrome. Cross‐industry evidence from 2502 German firms underlines the critical role of collaboration governance—a contingency factor that is at the heart of the relational view, yet has remained surprisingly absent from the open innovation debate so far.